1986
DOI: 10.1152/jn.1986.55.6.1221
|View full text |Cite
|
Sign up to set email alerts
|

Movement and electromyographic disorders associated with cerebellar dysmetria

Abstract: The objective of these experiments was to determine whether dysmetric elbow flexions, which occurred during cerebellar dysfunction, had the same kinematic and electromyographic characteristics as movements of the same amplitude and velocity performed under normal conditions. Reversible cerebellar lesions were produced by cooling through two probes implanted on either side of the dentate nucleus in five Cebus albifrons monkeys. Normal, fast, and accurate elbow flexions had single-peaked velocities and a bi- or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(87 citation statements)
references
References 0 publications
6
80
0
1
Order By: Relevance
“…33 Yet, upon dentate cooling during movements at the elbow, Flament and Hore reported not only action tremor but in addition, hypermetria. 7 Their inclusion of hypermetria may be a matter of definition. Flament and Hore defined the endpoint of movement as the position at which velocity first reaches zero.…”
Section: Figure 3 -Shoulder and Elbow Movements In Normal Pointing Amentioning
confidence: 99%
“…33 Yet, upon dentate cooling during movements at the elbow, Flament and Hore reported not only action tremor but in addition, hypermetria. 7 Their inclusion of hypermetria may be a matter of definition. Flament and Hore defined the endpoint of movement as the position at which velocity first reaches zero.…”
Section: Figure 3 -Shoulder and Elbow Movements In Normal Pointing Amentioning
confidence: 99%
“…Recordings from the patient showed a number of abnormal features in the temporal profiles for angular velocities at the shoulder and elbow. In experiments involving cooling of cerebellar nuclei in monkeys, Flament and Hore 16 observed that the velocity profile for rapid elbow flexion movements became asymmetric with longer acceleration phases and shorter deceleration phases. In human subjects with a variety of cerebellar disorders, Brown et al 17 found abnormalities of velocity profiles for single joint target -directed movements.…”
Section: Reaching Movementsmentioning
confidence: 99%
“…Motor disability in essential tremor results predominantly from the complex interaction of postural-, action-and intention-tremor with goal-directed hand movements, but $10-15% of patients additionally present mild cerebellar symptoms, such as saccadic abnormalities (Helmchen et al, 2003), dysmetria or impaired tandem gait (Flament and Hore, 1986;Hallett et al, 1991;Fasano et al, 2010). There is an ongoing debate on whether a cerebellar dysfunction in essential tremor is caused by disease progression and neurodegeneration (Louis et al, 2007) or a functional disruption of the cerebello-thalamo-cortical network through the interference of tremor-related neuronal oscillations with normal cerebellar timing function (Solomon et al, 1994;Elble, 1998;Deuschl et al, 2000;Blangero et al, 2009;Elble, 2009).…”
Section: Introductionmentioning
confidence: 99%